Augmented Reality (AR) Media To Improve Interest In Learning Science In Elementary Schools - Siagian, Yosua Marasi Parningotan; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Jurnal Ilmu Sosial Mamangan, 2025)
Learning media is an innovation to respond to the educational revolution. Innovation in learning media is a strategic step to face changes in education. The ongoing development of learning media plays a role in increasing student interest and learning outcomes. The implementation of Augmented Reality (AR) technology in natural science education is anticipated to enhance scientific literacy, particularly among elementary school students. By incorporating three-dimensional media, the approach becomes more adaptable, interactive, and innovative, leveraging various objects as target markers. The objective of this study is to investigate and assess the implementation of Augmented Reality (AR) media in teaching natural science subjects in elementary schools. The research method employed is a literature review, utilizing a literature study approach for data collection. The development and use of AR media in various natural science topics have shown numerous positive effects on enhancing students' interest and learning outcomes. These topics include learning about animal diets, ecosystems, plants, and animals that undergo complete metamorphosis, among others. Consequently, students can foster creative qualities, gauge their emotional intelligence, and become more competitive and collaborative with their peers.